Comparative Analysis of the Incidence, Diagnosis and Treatment of Prostate Cancer between China and the United States - Wang, Ye; Li, Xuemei; You, Zongbing (Serican Journal of Medicine, 2025)
In the context of globalization and an aging population, prostate cancer has emerged as a significant threat to male health, with its incidence and mortality rates on the rise worldwide. Particularly in comparison between China and the United States, two representative countries, there are notable differences in the incidence, diagnosis, and treatment of prostate cancer due to variations in medical resource allocation, diagnostic techniques, lifestyles, and cultural perceptions. This article aims to compare and analyze the current status of prostate cancer in China and the U.S., explore the key factors influencing these differences, and provide references for the development of prostate cancer prevention and control strategies in China. We employ multi-dimensional data collection and analysis approaches including literature review, case-control studies, and statistical analysis. We focus on the epidemiological data, clinical practice guidelines, patient quality of life, and medical economic burden to comprehensively dissect the differences and their causes in prostate cancer management between China and the U.S. Our findings highlight the disparities between the two countries in the aspects of early screening, treatment preference, and long-term follow-up mechanisms, aiming to uncover the underlying reasons behind these differences and propose corresponding improvement suggestions. Conclusions drawn from our analyses indicate that the U.S. is relatively advanced in early diagnosis and personalized treatment of prostate cancer, benefiting from a more comprehensive healthcare system and advanced medical technologies. Although China has made a significant progress in recent years, it still faces many challenges due to the uneven distribution of medical resources, and there is space for improvement in public health awareness. The significance of our analysis lies in providing empirical evidence for formulating more scientifically sound and reasonable strategies for the prevention and control of prostate cancer in China, which will help promote further development and improvement in this field.